Protein D of Haemophilus influenzae is not a universal immunoglobulin D-binding protein. - Sasaki, K (1993)
Haemophilus influenzae type b and nontypeable H. influenzae have been reported to bind human immunoglobulin D (IgD). IgD myeloma sera from five patients were tested for the ability of IgD to bind to H. influenzae. Serotype b strains bound human IgD in four of the five sera tested. IgD in the fifth serum bound strongly to type b strain MinnA but poorly to other type b strains. Additionally, IgD binding was not observed when nontypeable strains were tested. The gene for protein D, the putative IgD-binding protein, was cloned from the IgD-binding H. influenzae type b strain MinnA and expressed in Escherichia coli. IgD binding to E. coli expressing protein D was not demonstrable. Recombinant protein D was purified, and antisera were generated in rabbits. Using these rabbit sera, we detected protein D in nontypeable as well as serotype b strains by Western blotting (immunoblotting). In contrast, IgD myeloma protein 4490, which was previously reported to bind to protein D by Ruan and coworkers (M. Ruan, M. Akkoyunlu, A. Grubb, and A. Forsgren, J. Immunol. 145:3379-3384), bound strongly to both type b and nontypeable H. influenzae as well as to E. coli expressing protein D. Thus, IgD binding is a general property of H. influenzae type b strains but not a general property of nontypeable strains, although both type b and nontypeable strains produce protein D. With the exception of IgD myeloma protein 4490 binding, we have no evidence for a role of protein D in IgD binding to H. influenzae.